Occurrence of diazotrophic bacteria in different sugar cane genotypes - Reis Junior, Fábio Bueno dos; Silva, Lucia Gracinda da; Reis, Verônica Massena; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to find out the localization and number of endophytic bacteria in four sugar cane genotypes and investigate upon the possible existence of correlation to the results obtained in some studies about quantification of biological nitrogen fixation (BNF). A survey of the diazotrophic bacteria present in sugar cane genotypes differing in their capacity to obtain nitrogen through BNF was performed, and population of Herbaspirillum spp. and Acetobacter diazotrophicus was quantified. The bacteria tested in the survey were Azospirillum lipoferum, A. brasilense, A. amazonense, Herbaspirillum spp. and Acetobacter diazotrophicus. All these bacteria were present in the four genotypes and were found in all parts of the plants, except A. amazonense which was not isolated from leaf samples. The quantification of Herbaspirillum spp. and A. diazotrophicus showed that there were no significant differences among the sugar cane genotypes and, generally, the bacteria were in greater number in roots. While number of Herbaspirillum spp. remained stable during the life-cycle of the culture, the population of A. diazotrophicus suffer a decrease with the approach of the end of the commercial cycle. It is suggested that the differences in the rates of BNF found in sugar cane genotypes are not caused by differences in the presence or the number of the bacterial species studied here.